Factors affecting cassava consumption in an urban population in Zambia - Mushingwani, Stanley (Kansas State University, 2009)
Maize is a staple food to many Zambians. It is for this reason that it has received a lot of support from government as a way of maintaining food security in the nation. No other crop in Zambia currently receives such level of support from government. Factors influencing its availability can thus seriously affect food security. In recent years, Zambia has not been spared by adverse climatic changes that have continued to affect the entire globe. In the early 1980s the southern “maize-belt” part of the country that was devastated by continuous drought that caused villagers to go hungry and lose a lot of livestock that was their main livelihood. The trend of decreasing rainfall in consecutive seasons has continued in many parts of the country. Because most smallholder farmers, who are the major contributors to the nation’s food supply, depend on rain for crop production, there has been a deliberate policy by government through the Ministry of Agriculture and Co-operatives to encourage the farmers to diversify their on- and off-farm activities to improve food security at household and national level. To this end, the government has continued to encourage the growing of cassava. Several studies have suggested that cassava is a nutritious food crop (Chitundu, Droppelman and Haggblade, 2006). Cassava has a number of industrial uses too. Good attributes of cassava lie not only in the nutrition content of the tuber and leaves but also in the fact that as a field crop it does not require expensive inputs like fertilizer and is better able to withstand drought compared to the maize crop. This study attempts to understand the economic factors that influence consumption of cassava to shed light on its potential to avert potential crisis associated with prolonged droughts. Based on the survey conducted in 2007 in Lusaka, the study found that price and quality of cassava meal are the principal determinants of cassava meal demand in Lusaka. Direct price elasticity of demand for cassava is -1.32, suggesting that cassava meal is price elastic. The study also found that the cross price elasticity between maize meal price and cassava meal demand is 0.04 suggesting that cassava meal is a substitute to maize meal, but inelastic. The income price elasticity of demand for cassava meal is -0.12. However, income was found to be statistically insignificant in determining the demand for cassava meal. As such these economic factors are keys to the consumption of cassava. Therefore, the study suggests that the demand for cassava meal in Zambia may be improved through deliberate promotion.
Keywords: Cassava consumption in Zambia; Economics, Agricultural (0503)